Tension band high-strength suture combined with absorbable cannulated screws for treating transverse patellar fractures: finite element analysis and clinical study - Xiang, Feifan; Xiao, Yukun; Li, Dige; Ma, Wenzhe; Chen, Yue; Yang, Yunkang (Frontiers in Bioengineering and Biotechnology, 2024)
Objective: Few reports exist on the treatment of transverse patellar fractures (TPFs) using absorbable cannulated screws and high-strength sutures, and most screws and sutures lack good biomechanics and clinical trials. Therefore, this study aimed to demonstrate the biomechanical stability and clinical efficacy of tension-band high-strength sutures combined with absorbable cannulated screws (TBSAS) in treating TPFs (AO/OTA 34 C1). Methods: Finite element models of five internal fixation schemes were established: tension-band wire with K-wire (TBW), TBW with cerclage wire (TBWC), TBW with headless pressure screws (TBWHS), TBW with full-thread screws (TBWFS), and TBSAS. We comprehensively compared the biomechanical characteristics of the TBSAS treatment scheme during knee flexion and extension. Forty-one patients with TPFs in our hospital between January 2020 and August 2022 were retrospectively enrolled and divided into the TBSAS (n = 22) and TBWC (n = 19) groups. Clinical and follow-up outcomes, including operative time, visual analog scale (VAS) pain score, postoperative complications, Bostman score, and final knee range of motion, were compared between both groups. Results: Finite element analysis (FEA) showed that TBWHS and TBWFS achieved the minimum mean fracture interface relative displacement during knee flexion (45°, 0–500 N bending load) and full extension (0°, 0–500 N axial load). There was no significant difference between TBSAS (0.136 mm) and TBWC (0.146 mm) during knee flexion (500 N); however, TBSAS displacement was smaller (0.075 mm) during full extension (500 N). Furthermore, the stress results for the internal fixation and the patella were generally lower when using TBSAS. Retrospective clinical studies showed that the TBSAS group had a shorter operative time, lower VAS pain score at 1 and 2 months postoperatively, better Bostman knee function score at 3 and 9 months postoperatively, and better final knee joint motion than the TBWC group (all p < 0.05). There were five cases (26.3%) of internal fixation stimulation complications in the TBWC group. Conclusion: TBSAS demonstrated excellent safety and effectiveness in treating TPFs. It is sufficient to meet the needs of TPF fixation and early functional exercise and effectively reduces metal internal fixation-induced complications and secondary surgery-induced trauma.